Deteksi Dini Penyakit HIV-AIDS, Sifilis dan Hepatitis B dengan Pemeriksaan Triple Eliminasi pada Ibu Hamil: Early Detection of HIV-AIDS, Syphilis, and Hepatitis B with Triple Elimination Examination in Pregnant - Fatmawati, Ariani; Imansari, Bhekti; Renjani, Renjani; Salma, Citra; Apriani, Syifa; Laila, Neng; Putri, Hanny Anisa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Pregnant women are one of the populations at risk of transmitting HIV-AIDS, Hepatitis B, and Syphilis to their children during pregnancy. This activity aims to increase pregnant women's knowledge about and implementing triple elimination examinations. The activity method involves audio-visual counseling and triple elimination examination. The results showed increased knowledge; 76.3% had good knowledge, and 23.7% had sufficient knowledge. The results of the examination showed that 100% of pregnant women (30 people) were non-reactive for HIV, syphilis, and hepatitis B. Audio-visual education was effective in increasing knowledge so that awareness of pregnant women to carry out triple elimination examinations increased. It is recommended that the counseling video be played continuously in the waiting room.